Motivation and self-efficacy in cycling and running athletes: a person-centered approach - Tokarska, Elżbieta; Rogowska, Aleksandra M. (Frontiers in Psychology, 2025)
IntroductionThe study aims to examine the motivation and self-efficacy of athletes who are practicing cycling and running using the person-centered approach.MethodsA sample of 156 professional athletes (73 cyclists and 83 runners), including 65% of men, participated in the cross-sectional study. The mean age of athletes was 32 years old, ranging from 18 to 64 (M = 31.68, SD = 11.26). The online survey included the Sports Motivation Scale (SMS-28) and the Generalized Self-Efficacy Scale (GSES) to assess self-reported motivation for sports activity and the general sense of self-efficacy.ResultsThe K-means cluster analysis identified three groups of athletes based on their scores in sports motivation and self-efficacy. The first sample included “Internally motivated athletes,” who scored high in self-efficacy and three scales of intrinsic motivation (to know, to accomplish, and to experience stimulation) and simultaneously scored low in three scales of external motivation (introjected, identified, and external regulation), and amotivation. The second group comprised “Externally motivated athletes,” scoring high in all dimensions of extrinsic motivation while low in intrinsic motivation scales and self-efficacy. The third group of “Highly motivated athletes” scored high on self-efficacy and all dimensions of sports motivation. The multivariate analysis of variance (MANOVA) and one-way ANOVA showed several differences in sports motivation and self-efficacy between particular clusters.DiscussionClassifying athletes into three groups based on their motivation and self-efficacy can be utilized in sports psychology. In particular, those externally motivated athletes require psychological support to increase their intrinsic motivation and self-efficacy.